THE INFLUENCE OF EMPLOYEE PLACEMENT ON THE PERFORMANCE OF SOCIAL AFFAIRS OFFICE OF WAROPEN REGENCY PAPUA PROVINCE - Samori, Giosantho Atmawan; Nangameka, Teresa Irmina (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
Problem (GAP): Providing optimal performance and maintaining a competitive advantage are the primary goals of dynamic organizations. The most potential and critical factor in designing strategies to excel in organizational competition is human resources, and this depends on the proper adaptation of these resources to align with organizational goals. Poor positioning can be problematic for an organization. In this context, the Social Affairs Office (Dinsos) of Waropen Regency faces a mismatch between the employees' skills and the tasks, principles, and functions of the organization. Objective: To identify, analyze, and describe whether job placement affects the performance of employees at the Social Affairs Office of Waropen Regency, Papua Province. Method: This study used a quantitative approach to examine the influence of the independent variable on the dependent variable. The dependent variable in this study was employee performance, and the independent variable was employee placement. Results/Findings: The study found that job placement significantly affects employee performance, as indicated by the t- value of 7.847 which is higher than the t-table value of 2.10982. Therefore, H0 is rejected and H1 is accepted, indicating that employee placement partially influences performance. The better the employee placement the higher the satisfaction level which leads to positive impacts on the employees' performance. Conclusion: Employee placement significantly affects performance improvement by 77.4%, with the remaining 22.6% influenced by other variables outside this study. The regression line equation is y= a + bx, where y = 13.870 + 0.806, indicating that a 1% increase in b results in a corresponding increase in the employee performance variable.